2005
DOI: 10.1590/s1678-97412005000300013
|View full text |Cite
|
Sign up to set email alerts
|

<![CDATA[<B>Evaluation of pulmonary function in patients following on and off-pump coronary artery bypass grafting</B>]]>

Abstract: Avaliação da função pulmonar em pacientes submetidos à cirurgia de revascularização do miocárdio com e sem circulação extracorpórea

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
4
17
0
1
Order By: Relevance
“…[19][20][21][22][23][24] Similar results were found in our study. Conventionally, coronary artery bypass grafting involves trauma to the rib cage, which causes pain that can be intensified by coughing.…”
Section: Discussionsupporting
confidence: 89%
“…[19][20][21][22][23][24] Similar results were found in our study. Conventionally, coronary artery bypass grafting involves trauma to the rib cage, which causes pain that can be intensified by coughing.…”
Section: Discussionsupporting
confidence: 89%
“…After surgery, there is a 40% to 60% drop in volumes and capacities in relation to preoperative values [8,9]. Several factors are responsible for this postoperative pulmonary dysfunction.…”
Section: Data Expressed As Mean ± Standard Deviation P Values For Comentioning
confidence: 99%
“…The emergence of OPCAB techniques have minimized intraoperative and postoperative complications, resulting in shorter hospitalization. Guizilini et al [8] demonstrated that patients underwent off-pump surgery had better preservation of pulmonary function when compared to those on-pump. Recently, Silva et al [12] demonstrated that significant deterioration in lung function occurs following either on-and off-pump CABG.…”
Section: Data Expressed As Mean ± Standard Deviation P Values For Comentioning
confidence: 99%
See 1 more Smart Citation
“…Já no pós-operatório merecem destaque, além da diminuição da estabilidade e complacência da parede torácica pela esternotomia mediana, 11,15 os longos períodos em decú-bito dorsal, à presença de dor 11 e drenos implicando, diretamente, na manutenção de baixos volumes pulmonares. 4,6,12,16,20,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Devido ao quadro de disfunção pulmonar associado à CC e suas possíveis repercussões, a fisioterapia respiratória (FiR) tem sido muito utilizada com o intuito de reverter ou amenizar tal quadro, evitando o desenvolvimento de complicações pulmonares, pela utilização de grande variedade de técnicas. 4,6,8,9,16,21,22,29,32,[43][44][45][46] Sua atuação inicia-se com o "desmame" ventilatório e estende-se até a manutenção do paciente em ventilação espontânea após extubação.…”
Section: Palavrasunclassified